2008
DOI: 10.1177/112067210801800203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pterygium Surgery on Corneal Topography

Abstract: Corneal topographic changes caused by the pterygium are almost reversible after surgical treatment. Successful pterygium surgery significantly reduces topographic astigmatism, SRI, SAI, and corneal flattening. However, precise prediction of these refractive changes is not always accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 11 publications
5
41
0
2
Order By: Relevance
“…[28,46]). Errais et al recently demonstrated that the astigmatism in 20 eyes with pterygium, treated with surgical excision, was reduced from 5.47 ± 3.45 D to 1.79 ± 1.52 D and BCVA increased from 0.73 ± 0.20 to 0.89 ± 0.16 [17]. Bahar et al, in a similar study of 55 eyes with primary pterygium, came with almost the same results.…”
Section: Discussionsupporting
confidence: 68%
“…[28,46]). Errais et al recently demonstrated that the astigmatism in 20 eyes with pterygium, treated with surgical excision, was reduced from 5.47 ± 3.45 D to 1.79 ± 1.52 D and BCVA increased from 0.73 ± 0.20 to 0.89 ± 0.16 [17]. Bahar et al, in a similar study of 55 eyes with primary pterygium, came with almost the same results.…”
Section: Discussionsupporting
confidence: 68%
“…Even without involvement of the optical zone, pterygium can produce significant alterations in corneal shape and curvature. Thus, many studies have shown that pterygium is associated with regular and irregular astigmatism as well as changes in corneal curvature and refractive status, which improve at least in part after the surgery [1][2][3][4][5][6][7][8][9][10][11][12][13]. Corneal curvature in these studies has been investigated with corneal topography, which evaluates the front corneal surface.…”
Section: Introductionmentioning
confidence: 99%
“…1 Contrary to our results, some studies show no correlation between these 2 parameters. 19,20,21 ,This contradiction might be related to the larger horizontal pterygium sizes in present study In conclusion, pterygium results in high corneal astigmatism, which increases with the increase in horizontal length, and decreases to an acceptable level following excision. We found a significant correlation between the preoperative and postoperative astigmatic values as well as the changes in astigmatism with surgery…”
Section: Discussionmentioning
confidence: 66%